Possible Dissemination of Escherichia coli Sequence Type 410 Closely Related to B4/H24RxC in Ghana - Mahazu, Samiratu; Prah, Isaac; Ayibieke, Alafate; Sato, Wakana; Hayashi, Takaya; Suzuki, Toshihiko; Iwanaga, Shiroh; Ablordey, Anthony; Saito, Ryoichi (Frontiers in Microbiology, 2021)
Extra-intestinal pathogenic Escherichia coli (ExPEC) is one of the world’s leading causes of bloodstream infections with high mortality. Sequence type 410 (ST410) is an emerging ExPEC clone resistant to a wide range of antibiotics. In this study, we investigated the epidemiology of 21 ST410 E. coli isolates from two Ghanaian hospitals. We also investigated the isolates within a global context to provide further insight into the dissemination of this highly pathogenic clone. A phylogenetic tree of the 21 isolate genomes, along with 102 others from global collection, was constructed representing the ensuing clades and sub-clades of the ST: A/H53, B2/H24R, B3/H24Rx, and B4/H24RxC. The carbapenem-resistant sub-clade B4/H24RxC is reported to have emerged in the early 2000s when ST410 acquired an IncX3 plasmid carrying a blaOXA-181 carbapenemase gene, and a second carbapenemase gene, blaNDM-5, on a conserved IncFII plasmid in 2014. In this study, we identified one blaOXA-181–carrying isolate belonging to B4/H24RxC sub-lineage and one carrying blaNDM-1 belonging to sub-lineage B3/H24Rx. The blaOXA-181 gene was found on a 51kb IncX3 plasmid; pEc1079_3. The majority (12/21) of our Ghanaian isolates were clustered with international strains described by previous authors as closely related strains to B4/H24RxC. Six others were clustered among the ESBL-associated sub-lineage B3/H24Rx and three with the globally disseminated sub-lineage B4/H24RxC. The results show that this highly pathogenic clone is disseminated in Ghana and, given its ability to transmit between hosts, it poses a serious threat and should be monitored closely.